A method and application of nanocomposite excitation solution to enhance the mineralization of solid waste materials
Through the nanocomposite excitation solution, the mineralization method of solid waste materials is strengthened, and the safety hazards of CO2 storage and low mineralization efficiency are solved in the coal mines, and the efficient CO2 absorption and mineralization are achieved. The generated solid waste filling materials have high strength and dense structures. , suitable for coal mine goaf support, improving working efficiency and carbon neutrality effect.
Patent Information
- Application Number
- CN202410606875.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-05-16
AI Technical Summary
The existing CO2 storage technology has safety hazards and low mineralization efficiency in coal mines, making it difficult to meet the trend of growing carbon emissions.
The mineralization method of solid waste materials is strengthened by using nanocomposite excitation solution. By adding sodium silicate and nano-scale silica particles to the sodium hydroxide solution, combined with ultrasonic oscillation and stirring, an alkaline excitation base liquid and solid material is formed to mix it with the solid material. Highly efficient CO2 absorption and mineralization.
The CO2 absorption rate and adsorption amount are improved, and the mineralized products produced have high-strength and dense microstructure, which can quickly fill and control the subsidence of covered rocks. They are suitable for the support of coal mine goafs, and improve working efficiency and carbon neutrality. .
Smart Images

Figure CN118545951B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for strengthening the mineralization of solid waste materials with a nano-composite excitation solution and application thereof, belonging to the technical field of solid waste-CO2 underground coal mine co-disposal. Background Art
[0002] CO2 storage in coal mines is a favorable way to solve carbon emissions. In the existing technology, CO2 gas is usually injected into the coal mine goaf through drilling and sealed under pressure, but this storage method has great safety hazards; during coal mining, the pressure in the mining area changes continuously, causing cracks in the surrounding rock around the working face. Injecting CO2 gas will face the problem of leakage, and the workload of sealing all cracks is huge and difficult to achieve, with poor economic benefits.
[0003] The above-mentioned problem can be effectively solved by mineralizing CO2 with solid waste material slurry at room temperature and pressure and sealing CO2 in the form of solid carbonate. However, the CO2 mineralization method without special treatment has low mineralization efficiency and cannot meet the growing trend of carbon emissions. Summary of the invention
[0004] In order to effectively solve the above problems, the present invention provides a method and application of strengthening the mineralization of solid waste materials with a nano-composite excitation solution. The method has simple steps, can efficiently and quickly consume CO2, and can quickly generate solids, thereby achieving the effect of rapid filling and controlling overburden settlement.
[0005] To achieve the above technical purpose, the present invention provides a method for strengthening the mineralization of solid waste materials with a nano-composite excitation solution, wherein sodium silicate is added to a sodium hydroxide solution with a concentration of 3-20% and stirred evenly to obtain an alkaline excitation solution; the mass ratio of sodium silicate to sodium hydroxide solution is (1-30):100, a polycarboxylic acid water reducer is mixed into the alkaline excitation solution until the content of the polycarboxylic acid water reducer in the alkaline excitation solution meets 0.01%-1%, thereby obtaining an alkaline excitation base liquid; nano-scale silica particles are finally added to the alkaline excitation base liquid and mixed to obtain a nano-composite excitation solution, wherein the mass ratio of the nano-scale silica particles to the alkaline excitation base liquid is (0.1-5):100, and the nano-composite excitation solution is added to the alkaline excitation base liquid. The excitation solution is controlled to be ultrasonically oscillated at room temperature until it becomes transparent, fly ash and coal gangue are ground to nanometer level and then mixed in a mass ratio of (1-10):1 to obtain solid material, and then mixed in a mass ratio of (1-5):10 of nano-excitation solution to solid material to obtain solid waste material slurry, and then carbon dioxide gas is introduced into the solid waste material slurry while stirring to achieve mineralization; nano-scale silica particles are added to the excitation solution to increase the gas-liquid two-phase interface area of the solid waste material slurry and improve the diffusion coefficient of Brownian motion. At the same time, the nano-scale silica particles provide nucleation sites to better adsorb carbon dioxide, and the mineralization efficiency of carbon dioxide can be improved during the stirring process.
[0006] The specific steps are as follows:
[0007] Step 1, adding sodium hydroxide particles into water, the mass ratio of sodium hydroxide to water is (3-20):100, mixing and stirring evenly until the sodium hydroxide is completely dissolved in the water, to obtain a sodium hydroxide solution; after the temperature of the sodium hydroxide solution drops to room temperature, adding sodium silicate into the sodium hydroxide solution, the mass ratio of sodium silicate to the sodium hydroxide solution is (1-30):100, mixing and stirring evenly to obtain an alkaline exciting solution;
[0008] Step 2, adding a polycarboxylate water reducer to the alkaline excitation solution, wherein the mass ratio of the polycarboxylate water reducer to the alkaline excitation solution is (0.01-1):100; mixing and stirring to obtain an alkaline excitation base solution;
[0009] Step 3, adding nano-scale silica particles to the alkaline excitation base liquid, the mass ratio of the nano-scale silica particles to the alkaline excitation base liquid is (0.1-5):100, and mixing and stirring to obtain a turbid nano-composite excitation solution;
[0010] Step 4, moving the turbid nanocomposite excitation solution to an ultrasonic instrument and performing ultrasonic treatment for 5 minutes to 240 minutes; during the period, the water in the ultrasonic treatment is replaced every 2 minutes to 5 minutes, so as to control the water temperature in the ultrasonic treatment process to be lower than 45°C, ensure that the nano-silicon dioxide is fully dispersed, and avoid excessive temperature causing the solution to lose activity; when the turbid nanocomposite excitation solution after ultrasonic treatment changes from a turbid state to a transparent state, the nanocomposite excitation solution is obtained after the stability is improved;
[0011] Step 5, grinding fly ash to a particle size of 0.1 μm to 250 μm, grinding coal gangue to a particle size of 1 μm to 1000 μm, and then mixing the fly ash and coal gangue in a mass ratio of (1 to 10): 1 to obtain a solid material;
[0012] Step 6, adding the nanocomposite excitation solution prepared in step 4 to the solid material in step 5, mixing and stirring to obtain a solid waste material slurry, wherein the mass ratio of the nanocomposite excitation solution to the solid material is (1-5):10;
[0013] Step 7: injecting carbon dioxide gas into the solid waste material slurry in the stirring device described in step 6 at normal temperature and pressure to carry out a mineralization reaction while stirring; during this period, the injected carbon dioxide flow rate and the outflowing carbon dioxide flow rate are recorded.
[0014] Furthermore, the sodium silicate Na2O·nSiO2 used in step 1 has a Na2O content of 10% to 21.4%, a SiO2 content of 25% to 40.7%, a pH of the alkaline excitation solution of 9 to 14, and a consistency coefficient of 2.1 mPa.s n ~8.4mPa.sn .
[0015] Furthermore, in step 3, the nano-silica particle size is 1.2nm to 300nm, the shape is an amorphous white powder, and the specific surface area is 120m / g to 300m / g; the stirring rate when added to the alkaline excitation base liquid is 500r / min to 1500r / min to ensure that the formed nano-composite excitation solution has a larger specific surface area; the frequency of the ultrasonic treatment in step 4 is 20kHz to 40kHz.
[0016] Furthermore, the mass ratios of the components in the fly ash used in step 5 are: CaO content (1.8-10.5):100, SiO2 content (40-65):100, Al2O3 content (21.3-47.8):100, and other components content (5.4-10.8):100; the components in the coal gangue used are: CaO content (0.2-5.9):100, SiO2 content (33.1-57.4):100, Al2O3 content (10.7-29.1):100, and other components content (29.6-33.5):100.
[0017] Furthermore, the stirring rate in step 6 is 120 r / min to 1000 r / min, the stirring time is 2 min to 10 min, the yield stress of the prepared solid waste material slurry is 1.2 Pa to 28.6 Pa, and the expansion is 300 mm to 470 mm, ensuring that the solid waste slurry has sufficient fluidity.
[0018] Furthermore, the flow rate of carbon dioxide injected into step 7 meets the requirements of 0.1L / min to 10L / min when the solid waste material slurry is 100g to 3500g, the stirring rate is 100r / min to 850r / min, the reaction time is 5min to 60min, and the carbon dioxide mineralization rate is 14.7mgCO2 / g filling material to 80.2mgCO2 / g filling material.
[0019] Further, the solid waste material slurry after the mineralization reaction in step 7 is poured into a mold, and then cured and solidified to obtain a solid waste filling material sample, the curing temperature is 20°C to 25°C, the curing humidity is 90% to 95%, and the compressive strength is 2.5MPa to 8.8MPa.
[0020] A solid waste filling material prepared by a method for strengthening the mineralization of solid waste materials using a nano-composite excitation solution.
[0021] An application of solid waste filling material, characterized in that: the solid waste material slurry after mineralization reaction is poured into a mold to make a goaf support structure; or the solid waste material slurry after mineralization reaction is poured into the goaf for carbon fixation and backfilling.
[0022] Beneficial effects: The present invention disperses nano-silicon dioxide in an alkaline excitation solution by ultrasonic treatment to develop a nano-composite excitation solution, which is added to the solid waste material slurry, which is beneficial to improving the mineralization efficiency of CO2 and slurry under normal temperature and pressure conditions, and quickly absorbs CO2 under normal temperature and pressure conditions. Compared with the existing materials without added nano-scale silicon dioxide particles, the nano-composite excitation solution of this method has a CO2 absorption rate of 15% higher than that of the existing materials without added nano-scale silicon dioxide particles, and the CO2 adsorption capacity is 30% higher. At the same time, the mineralized carbonate products and the silica gel hydrated by the nanoparticles produced can reach 90% of the strength within 3 days under mine environmental conditions; and the solidified solid waste filling material has a dense microstructure, which can control the movement of overburden and fill it into the coal mine goaf, and can adapt to the continuous mining and continuous filling coal mining method, so as to achieve the effect of controlling the subsidence of overburden in a short period of time, improve work efficiency, effectively realize the joint disposal of solid waste and CO2, and contribute to the implementation of carbon neutrality.
[0023] Instruction Manual
[0024] Figure 1 Schematic diagram showing the comparison of mineralization rate and CO2 absorption rate of the nanocomposite excitation solution-enhanced solid waste material in the embodiment of the present invention and the comparative example;
[0025] Figure 2 A schematic diagram showing the comparison of the compressive strength and strength increase rate of the solid waste material strengthened by the nanocomposite excitation solution in the embodiment of the present invention and the comparative example;
[0026] Figure 3 Schematic diagram of the microstructure comparison between the nanocomposite excitation solution-reinforced solid waste material in the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION
[0027] The embodiments of the present invention are further described below:
[0028] The present invention discloses a method for strengthening the mineralization of solid waste materials using a nanocomposite excitation solution, and the specific steps include:
[0029] Step 1, adding sodium hydroxide particles into water, mixing and stirring to obtain a sodium hydroxide solution; after the temperature of the sodium hydroxide solution drops to room temperature, adding sodium silicate into the sodium hydroxide solution, mixing and stirring to obtain an alkaline excitation solution;
[0030] Step 2, adding the polycarboxylate water-reducing agent to the alkaline excitation solution prepared in step 1, mixing and stirring to obtain an alkaline excitation base solution;
[0031] Step 3, adding nano-silicon dioxide to the alkaline excitation base liquid prepared in step 2, mixing and stirring to obtain a turbid nano-composite excitation solution for standby use;
[0032] Step 4, moving the turbid nanocomposite excitation solution prepared in step 3 to an ultrasonic instrument for ultrasonic treatment; during this period, in order to prevent the water temperature from being too high due to heat generated during the ultrasonic treatment, the water in the ultrasonic treatment bath needs to be replaced regularly; when the solution changes from a turbid state to a transparent state, a nanocomposite excitation solution is obtained;
[0033] Step 5, grinding the fly ash and coal gangue, and mixing them evenly to obtain a solid material;
[0034] Step 6, adding the nanocomposite excitation solution prepared in step 4 to the solid material in step 5, mixing and stirring in a stirring device to obtain a solid waste material slurry;
[0035] Step 7, injecting carbon dioxide gas into the solid waste material slurry in the stirring device described in step 6 at normal temperature and pressure to carry out a mineralization reaction while stirring; during which, the flow rate of injected carbon dioxide and the flow rate of outflowing carbon dioxide are recorded;
[0036] Step 8: Pour the solid waste material slurry after the mineralization reaction in step 7 into a mold, and then obtain a solid waste filling material sample after curing and solidification, and perform a compressive strength test and a microstructure analysis.
[0037] As a specific implementation, in step 1, the Na2O content in the sodium silicate is 10% to 21.4%, the SiO2 content is 25% to 40.7%, the pH of the alkaline exciting solution is 9 to 14, and the consistency coefficient is 2.1 mPa.s n ~8.4mPa.s n , thereby ensuring that the alkaline stimulating solution is sufficiently active.
[0038] As a specific implementation, in step 2, the content of the polycarboxylate water-reducing agent in the alkaline excitation solution is 0.01% to 1%, thereby ensuring the dispersion effect when nano-silicon dioxide is further added.
[0039] As a specific implementation, in step 3, the nano-silica particle size is 1.2nm to 300nm, the shape is an amorphous white powder, the specific surface area is 120m / g to 300m / g, and the stirring rate is 500r / min to 1500r / min, thereby ensuring that the formed nano-composite excitation solution has a larger specific surface area.
[0040] As a specific implementation, the frequency of the ultrasonic treatment in step 4 is 20kHz to 40kHz, and the ultrasonic treatment temperature is lower than 45°C, thereby ensuring that the nano-silicon dioxide is fully dispersed and that the solution loses its activity due to excessively high temperature.
[0041] As a specific implementation, in step 5, the CaO content of the fly ash is 1.8% to 10.5%, the SiO2 content is 40% to 65%, the Al2O3 content is 21.3% to 47.8%, the content of the gangue is 0.2% to 5.9%, the SiO2 content is 33.1% to 57.4%, and the Al2O3 content is 10.7% to 29.1%, thereby ensuring that the solid material can fully react.
[0042] As a specific implementation, the stirring rate in step 6 is 120r / min~1000r / min, the stirring time is 2min~10min, the yield stress of the solid waste material slurry is 1.2Pa~28.6Pa, and the expansion is 300mm~470mm, thereby ensuring that the solid waste slurry has sufficient fluidity.
[0043] As a specific implementation, the flow rate of carbon dioxide injected in step 7 is 0.1L / min~10L / min, the stirring rate is 100r / min~850r / min, and the reaction time is 5min~60min, thereby ensuring that the solid waste slurry can fully absorb carbon dioxide and react with mineralization.
[0044] As a specific implementation, the carbon dioxide mineralization rate of the solid waste material slurry in step 7 is 14.7 mgCO2 / g filling material to 80.2 mgCO2 / g filling material.
[0045] As a specific implementation, in step 8, the curing temperature is 20° C. to 25° C., and the curing humidity is 90% to 95%, thereby ensuring that the solid waste filling material can be solidified in the underground mine environment.
[0046] As a specific implementation, the compressive strength of the solid waste filling material prepared in step 8 is 2.5 MPa to 8.8 MPa.
[0047] Example 1
[0048] In order to further understand the method for strengthening the mineralization of solid waste materials provided by the present invention, the following is a detailed description in conjunction with an embodiment, and the specific steps are as follows:
[0049] Step 1, adding sodium hydroxide to water at a mass ratio of 8.5:100 and uniformly mixing to form a sodium hydroxide solution; after the temperature of the sodium hydroxide solution drops to room temperature, adding sodium silicate to the sodium hydroxide solution at a mass ratio of 12.5:100 and uniformly mixing to form an alkaline exciting solution with a pH value of 14;
[0050] Step 2, adding the polycarboxylate water reducer to the alkaline excitation solution prepared in step 1 at a mass ratio of 0.75:100 and uniformly mixing to form an alkaline excitation base liquid;
[0051] Step 3, adding nano-silicon dioxide to the alkaline excitation base solution prepared in step 2 at a mass ratio of 0.5:100, stirring at a speed of 1200 r / min to uniformly mix into a turbid nano-composite excitation solution;
[0052] Step 4, moving the turbid nanocomposite excitation solution prepared in step 3 to an ultrasonic instrument and performing ultrasonic treatment at a frequency of 40 kHz. In order to prevent the water temperature from being too high due to heat generated during the ultrasonic treatment, the ultrasonic treatment temperature needs to be controlled below 45°C. When the solution changes from a turbid state to a transparent state, a nanocomposite excitation solution is obtained;
[0053] Step 5, grinding fly ash and coal gangue to particle sizes of 100 μm and 175 μm, adding fly ash and coal gangue in a mass ratio of 3:2 and mixing them evenly as a solid material;
[0054] Step 6: Add the nanocomposite excitation solution prepared in step 4 to the solid material in step 5 at a mass ratio of 1:3, and stir at a rate of 800 r / min for 5 minutes to obtain a solid waste material slurry. Then, the solid waste material slurry is subjected to a yield stress test and an expansion measurement;
[0055] Step 7, injecting carbon dioxide gas into the solid waste material slurry in the stirring device described in step 6 at a flow rate of 1 L / min under normal temperature and pressure conditions, and stirring the slurry at a rate of 500 r / min. The reaction time is 30 min; during this period, the injected carbon dioxide flow rate and the outflowing carbon dioxide flow rate are recorded;
[0056] Step 8. Pour the solid waste material slurry after the mineralization reaction in step 7 into a 50mm×100mm (columnar) mold, and then compact the specimen on a vibrating table. Place the molded specimen in a standard constant temperature and humidity curing box at a temperature of 25±2°C and a humidity of 95±5% for standard curing for 48 hours, and then demold it. After demolding, number the test blocks and continue to place them in the curing box for curing until the curing age reaches 28 days. After reaching the curing age, the columnar test blocks are subjected to a uniaxial compressive test to test the compressive strength of the test blocks, as well as microstructural analysis.
[0057] Example 2
[0058] In order to further understand the method for strengthening the mineralization of solid waste materials provided by the present invention, the following is a detailed description in conjunction with an embodiment, and the specific steps are as follows:
[0059] Step 1, adding sodium hydroxide to water at a mass ratio of 8.5:100 and uniformly mixing to form a sodium hydroxide solution; after the temperature of the sodium hydroxide solution drops to room temperature, adding sodium silicate to the sodium hydroxide solution at a mass ratio of 12.5:100 and uniformly mixing to form an alkaline exciting solution with a pH value of 14;
[0060] Step 2, adding the polycarboxylate water reducer to the alkaline excitation solution prepared in step 1 at a mass ratio of 0.75:100 and uniformly mixing to form an alkaline excitation base liquid;
[0061] Step 3, adding nano-silicon dioxide to the alkaline excitation base solution prepared in step 2 at a mass ratio of 1:100, stirring at a speed of 1200 r / min to uniformly mix into a turbid nano-composite excitation solution;
[0062] Step 4, moving the turbid nanocomposite excitation solution prepared in step 3 to an ultrasonic instrument and performing ultrasonic treatment at a frequency of 40 kHz. In order to prevent the water temperature from being too high due to heat generated during the ultrasonic treatment, the ultrasonic treatment temperature needs to be controlled below 45°C. When the solution changes from a turbid state to a transparent state, a nanocomposite excitation solution is obtained;
[0063] Step 5, grinding fly ash and coal gangue to particle sizes of 100 μm and 175 μm, adding fly ash and coal gangue in a mass ratio of 3:2 and mixing them evenly as a solid material;
[0064] Step 6: Add the nanocomposite excitation solution prepared in step 4 to the solid material in step 5 at a mass ratio of 1:3, and stir at a rate of 800 r / min for 5 minutes to obtain a solid waste material slurry. Then, the solid waste material slurry is subjected to a yield stress test and an expansion measurement;
[0065] Step 7, injecting carbon dioxide gas into the solid waste material slurry in the stirring device described in step 6 at a flow rate of 1 L / min under normal temperature and pressure conditions, and stirring the slurry at a rate of 500 r / min. The reaction time is 30 min; during this period, the injected carbon dioxide flow rate and the outflowing carbon dioxide flow rate are recorded;
[0066] Step 8. Pour the solid waste material slurry after the mineralization reaction in step 7 into a 50mm×100mm (columnar) mold, and then compact the specimen on a vibrating table. Place the molded specimen in a standard constant temperature and humidity curing box at a temperature of 25±2°C and a humidity of 95±5% for standard curing for 48 hours, and then demold it. After demolding, number the test blocks and continue to place them in the curing box for curing until the curing age reaches 28 days. After reaching the curing age, the columnar test blocks are subjected to a uniaxial compressive test to test the compressive strength of the test blocks, as well as microstructural analysis.
[0067] Example 3
[0068] In order to further understand the method for strengthening the mineralization of solid waste materials provided by the present invention, the following is a detailed description in conjunction with an embodiment, and the specific steps are as follows:
[0069] Step 1, adding sodium hydroxide to water at a mass ratio of 8.5:100 and uniformly mixing to form a sodium hydroxide solution; after the temperature of the sodium hydroxide solution drops to room temperature, adding sodium silicate to the sodium hydroxide solution at a mass ratio of 12.5:100 and uniformly mixing to form an alkaline exciting solution with a pH value of 14;
[0070] Step 2, adding the polycarboxylate water reducer to the alkaline excitation solution prepared in step 1 at a mass ratio of 0.75:100 and uniformly mixing to form an alkaline excitation base liquid;
[0071] Step 3, adding nano-silicon dioxide to the alkaline excitation base solution prepared in step 2 at a mass ratio of 1.5:100, stirring at a speed of 1200 r / min to uniformly mix into a turbid nano-composite excitation solution;
[0072] Step 4, moving the turbid nanocomposite excitation solution prepared in step 3 to an ultrasonic instrument and performing ultrasonic treatment at a frequency of 40 kHz. In order to prevent the water temperature from being too high due to heat generated during the ultrasonic treatment, the ultrasonic treatment temperature needs to be controlled below 45°C. When the solution changes from a turbid state to a transparent state, a nanocomposite excitation solution is obtained;
[0073] Step 5, grinding fly ash and coal gangue to particle sizes of 100 μm and 175 μm, adding fly ash and coal gangue in a mass ratio of 3:2 and mixing them evenly as a solid material;
[0074] Step 6: Add the nanocomposite excitation solution prepared in step 4 to the solid material in step 5 at a mass ratio of 1:3, and stir at a rate of 800 r / min for 5 minutes to obtain a solid waste material slurry. Then, the solid waste material slurry is subjected to a yield stress test and an expansion measurement;
[0075] Step 7, injecting carbon dioxide gas into the solid waste material slurry in the stirring device described in step 6 at a flow rate of 1 L / min under normal temperature and pressure conditions, and stirring the slurry at a rate of 500 r / min. The reaction time is 30 min; during this period, the injected carbon dioxide flow rate and the outflowing carbon dioxide flow rate are recorded;
[0076] Step 8. Pour the solid waste material slurry after the mineralization reaction in step 7 into a 50mm×100mm (columnar) mold, and then compact the specimen on a vibrating table. Place the molded specimen in a standard constant temperature and humidity curing box at a temperature of 25±2°C and a humidity of 95±5% for standard curing for 48 hours, and then demold it. After demolding, number the test blocks and continue to place them in the curing box for curing until the curing age reaches 28 days. After reaching the curing age, the columnar test blocks are subjected to a uniaxial compressive test to test the compressive strength of the test blocks, as well as microstructural analysis.
[0077] Example 4
[0078] In order to further understand the method for strengthening the mineralization of solid waste materials provided by the present invention, the following is a detailed description in conjunction with an embodiment, and the specific steps are as follows:
[0079] Step 1, adding sodium hydroxide to water at a mass ratio of 8.5:100 and uniformly mixing to form a sodium hydroxide solution; after the temperature of the sodium hydroxide solution drops to room temperature, adding sodium silicate to the sodium hydroxide solution at a mass ratio of 12.5:100 and uniformly mixing to form an alkaline exciting solution with a pH value of 14;
[0080] Step 2, adding the polycarboxylate water reducer to the alkaline excitation solution prepared in step 1 at a mass ratio of 0.75:100 and uniformly mixing to form an alkaline excitation base liquid;
[0081] Step 3, adding nano-silicon dioxide to the alkaline excitation base liquid prepared in step 2 at a mass ratio of 2:100, stirring and mixing at a speed of 1200 r / min to form a turbid nano-composite excitation solution;
[0082] Step 4, moving the turbid nanocomposite excitation solution prepared in step 3 to an ultrasonic instrument and performing ultrasonic treatment at a frequency of 40 kHz. In order to prevent the water temperature from being too high due to heat generated during the ultrasonic treatment, the ultrasonic treatment temperature needs to be controlled below 45°C. When the solution changes from a turbid state to a transparent state, a nanocomposite excitation solution is obtained;
[0083] Step 5, grinding fly ash and coal gangue to particle sizes of 100 μm and 175 μm, adding fly ash and coal gangue in a mass ratio of 3:2 and mixing them evenly as a solid material;
[0084] Step 6: Add the nanocomposite excitation solution prepared in step 4 to the solid material in step 5 at a mass ratio of 1:3, and stir at a rate of 800 r / min for 5 minutes to obtain a solid waste material slurry. Then, the solid waste material slurry is subjected to a yield stress test and an expansion measurement;
[0085] Step 7, injecting carbon dioxide gas into the solid waste material slurry in the stirring device described in step 6 at a flow rate of 1 L / min under normal temperature and pressure conditions, and stirring the slurry at a rate of 500 r / min. The reaction time is 30 min; during this period, the injected carbon dioxide flow rate and the outflowing carbon dioxide flow rate are recorded;
[0086] Step 8. Pour the solid waste material slurry after the mineralization reaction in step 7 into a 50mm×100mm (columnar) mold, and then compact the specimen on a vibrating table. Place the molded specimen in a standard constant temperature and humidity curing box at a temperature of 25±2°C and a humidity of 95±5% for standard curing for 48 hours, and then demold it. After demolding, number the test blocks and continue to place them in the curing box for curing until the curing age reaches 28 days. After reaching the curing age, the columnar test blocks are subjected to a uniaxial compressive test to test the compressive strength of the test blocks, as well as microstructural analysis.
[0087] Example 5
[0088] In order to further understand the method for strengthening the mineralization of solid waste materials provided by the present invention, the following is a detailed description in conjunction with an embodiment, and the specific steps are as follows:
[0089] Step 1, adding sodium hydroxide to water at a mass ratio of 8.5:100 and uniformly mixing to form a sodium hydroxide solution; after the temperature of the sodium hydroxide solution drops to room temperature, adding sodium silicate to the sodium hydroxide solution at a mass ratio of 12.5:100 and uniformly mixing to form an alkaline exciting solution with a pH value of 14;
[0090] Step 2, adding the polycarboxylate water reducer to the alkaline excitation solution prepared in step 1 at a mass ratio of 0.75:100 and uniformly mixing to form an alkaline excitation base liquid;
[0091] Step 3, adding nano-silicon dioxide to the alkaline excitation base solution prepared in step 2 at a mass ratio of 2.5:100, stirring at a speed of 1200 r / min to uniformly mix into a turbid nano-composite excitation solution;
[0092] Step 4, moving the turbid nanocomposite excitation solution prepared in step 3 to an ultrasonic instrument and performing ultrasonic treatment at a frequency of 40 kHz. In order to prevent the water temperature from being too high due to heat generated during the ultrasonic treatment, the ultrasonic treatment temperature needs to be controlled below 45°C. When the solution changes from a turbid state to a transparent state, a nanocomposite excitation solution is obtained;
[0093] Step 5, grinding fly ash and coal gangue to particle sizes of 100 μm and 175 μm, adding fly ash and coal gangue in a mass ratio of 3:2 and mixing them evenly as a solid material;
[0094] Step 6: Add the nanocomposite excitation solution prepared in step 4 to the solid material in step 5 at a mass ratio of 1:3, and stir at a rate of 800 r / min for 5 minutes to obtain a solid waste material slurry. Then, the solid waste material slurry is subjected to a yield stress test and an expansion measurement;
[0095] Step 7, injecting carbon dioxide gas into the solid waste material slurry in the stirring device described in step 6 at a flow rate of 1 L / min under normal temperature and pressure conditions, and stirring the slurry at a rate of 500 r / min. The reaction time is 30 min; during this period, the injected carbon dioxide flow rate and the outflowing carbon dioxide flow rate are recorded;
[0096] Step 8. Pour the solid waste material slurry after the mineralization reaction in step 7 into a 50mm×100mm (columnar) mold, and then compact the specimen on a vibrating table. Place the molded specimen in a standard constant temperature and humidity curing box at a temperature of 25±2°C and a humidity of 95±5% for standard curing for 48 hours, and then demold it. After demolding, number the test blocks and continue to place them in the curing box for curing until the curing age reaches 28 days. After reaching the curing age, the columnar test blocks are subjected to a uniaxial compressive test to test the compressive strength of the test blocks, as well as microstructural analysis.
[0097] The performance of the solid waste filling materials prepared by the method of strengthening the mineralization of solid waste materials using a nano-composite excitation solution in Examples 1-5 was compared. The comparative examples in the following table were prepared according to the proportions of the examples, but without adding nano-silicon dioxide:
[0098] Table 1 Yield stress, expansion and CO2 absorption rate of solid waste filling materials after treatment with composite excitation solution
[0099]
[0100] Table 2 Compressive strength of solid waste filling materials after being treated with composite excitation solution at different curing times
[0101]
[0102] In Examples 1-5, the ratio of nano-scale silica particles to solution was increased from 0.5:100 to 2.5:100, wherein the yield stress decreased and the expansion increased from 0.5 to 1.5, indicating that the fluidity of the solid waste material slurry was improved. However, when the silica nanoparticles were increased from 1.5 to 2.5, the fluidity was significantly reduced. This is because when the dosage of nano-scale silica particles was low, the nanoparticles quickly consumed the OH in the solution. - , improve the reaction between solution and solid waste, help improve fluidity, but when the dosage is too high, due to the extremely high specific surface area of nanoparticles, nanoparticles absorb too much water in the slurry, resulting in poor fluidity. This situation also appears in the compressive strength of solid waste materials. When the dosage is between 0.5 and 2, the strength is significantly improved due to the filling of nanoparticles in the microstructure and the silica gel produced during the reaction process. However, after the dosage reaches 2.5, too many nanoparticles cause agglomeration between particles, and the expected effect cannot be achieved.
[0103] Example 1 is compared with the existing mineralized material without adding nano-sized silica particles as a comparative example. Figure 1 As shown, the nanocomposite excitation solution prepared by the method and subjected to ultrasonic vibration to a transparent state has a CO2 absorption rate of 15% higher than that of solid waste materials, and a CO2 adsorption capacity of 30% higher than that of solid waste materials. Figure 2 As shown, a large amount of carbonic acid products are produced and the silica gel produced after hydration of nanoparticles reaches 90% strength within 3 days under mine environment conditions, as shown in Figure 3 As shown, the left side is the existing material, and the right side is the microstructure of the finished product of Example 1 of the present invention. It can be clearly seen that the solidified solid waste filling material of Example 1 of the present invention has a dense microstructure, which can control the movement of overburden and fill it into the goaf of coal mines. It can be adapted to the continuous mining and continuous filling coal mining method, and can achieve the effect of controlling the settlement of overburden in a short period of time, improve work efficiency, effectively realize the joint disposal of solid waste and CO2, and contribute to the implementation of carbon neutrality.
Claims
1. A method for strengthening the mineralization of solid waste materials using a nanocomposite excitation solution, characterized in that: The specific steps are as follows: Step 1, adding sodium hydroxide particles into water, the mass ratio of sodium hydroxide to water is (3-20):100, mixing and stirring evenly until the sodium hydroxide is completely dissolved in the water, to obtain a sodium hydroxide solution; after the temperature of the sodium hydroxide solution drops to room temperature, adding sodium silicate into the sodium hydroxide solution, the mass ratio of sodium silicate to the sodium hydroxide solution is (1-30):100, mixing and stirring evenly to obtain an alkaline excitation solution; Step 2, adding a polycarboxylate water reducer to the alkaline excitation solution, wherein the mass ratio of the polycarboxylate water reducer to the alkaline excitation solution is (0.01-1):100; mixing and stirring to obtain an alkaline excitation base solution; Step 3, adding nano-scale silica particles to the alkaline excitation base liquid, the mass ratio of the nano-scale silica particles to the alkaline excitation base liquid being (0.1-5):100, and mixing and stirring to obtain a turbid nano-composite excitation solution; Step 4: Move the turbid nanocomposite excitation solution to an ultrasonic instrument and perform ultrasonic treatment for 5 to 240 minutes; during this period, the water in the ultrasonic treatment is replaced every 2 to 5 minutes, so as to control the water temperature during the ultrasonic treatment to be lower than 45 o C, ensuring that the nano-silica is fully dispersed and avoiding excessively high temperatures that cause the solution to lose activity; when the turbid nano-composite excitation solution treated with ultrasound changes from a turbid state to a transparent state, a nano-composite excitation solution is obtained after improving stability; Step 5, grinding fly ash to a particle size of 0.1 μm to 250 μm, grinding coal gangue to a particle size of 1 μm to 1000 μm, and then mixing the fly ash and coal gangue in a mass ratio of (1 to 10): 1 to obtain a solid material; Step 6, adding the nanocomposite excitation solution prepared in step 4 to the solid material in step 5, mixing and stirring to obtain a solid waste material slurry, wherein the mass ratio of the nanocomposite excitation solution to the solid material is (1-5):10; Step 7, injecting carbon dioxide gas into the solid waste material slurry in step 6 at room temperature and pressure to carry out a mineralization reaction while stirring; during which, the flow rate of injected carbon dioxide and the flow rate of outflowing carbon dioxide are recorded; By adding nano-scale silica particles to the excitation solution, the gas-liquid interface area of the solid waste material slurry is increased, the diffusion coefficient of Brownian motion is improved, and at the same time, the nano-scale silica particles provide nucleation sites to better adsorb carbon dioxide, thereby improving the mineralization efficiency of carbon dioxide during the stirring process.
2. The method for strengthening the mineralization of solid waste materials using a nanocomposite excitation solution according to claim 1, characterized in that: The sodium silicate Na2O·nSiO2 used in step 1 has a Na2O content of 10% to 21.4%, a SiO2 content of 25% to 40.7%, a pH of an alkaline exciting solution of 9 to 14, and a consistency coefficient of 2.1 mPa.s n ~8.4mPa.s n .
3. The method for strengthening the mineralization of solid waste materials using a nanocomposite excitation solution according to claim 1, characterized in that: In step 3, the nano-silicon dioxide has a particle size of 1.2 nm to 300 nm, an amorphous white powder shape, and a specific surface area of 120 m / g to 300 m / g; The stirring rate of adding the alkaline excitation base liquid is 500r / min to 1500r / min to ensure that the formed nano-composite excitation solution has a larger specific surface area; the frequency of the ultrasonic treatment in step 4 is 20kHz to 40kHz.
4. The method for strengthening the mineralization of solid waste materials using a nanocomposite excitation solution according to claim 1, characterized in that: The mass ratios of the components in the fly ash used in step 5 are: CaO content (1.8-10.5): 100, SiO2 content (40-65): 100, Al2O3 content (21.3-47.8): 100, and other components content (5.4-10.8): 100; the components in the coal gangue used are: CaO content (0.2-5.9): 100, SiO2 content (33.1-57.4): 100, Al2O3 content (10.7-29.1): 100, and other components content (29.6-33.5):
100.
5. The method for strengthening the mineralization of solid waste materials using a nanocomposite excitation solution according to claim 1, characterized in that: The stirring rate in step 6 is 120 r / min to 1000 r / min, the stirring time is 2 min to 10 min, the yield stress of the prepared solid waste material slurry is 1.2 Pa to 28.6 Pa, and the expansion is 300 mm to 470 mm, ensuring that the solid waste slurry has sufficient fluidity.
6. The method for strengthening the mineralization of solid waste materials using a nanocomposite excitation solution according to claim 1, characterized in that: The flow rate of carbon dioxide injected into step 7 meets the requirements of 0.1L / min~10L / min when the solid waste material slurry is 100g~3500g, the stirring rate is 100r / min~850r / min, the reaction time is 5min~60min, and the carbon dioxide mineralization rate is 14.7mgCO2 / g filling material~80.2mgCO2 / g filling material.
7. The method for strengthening the mineralization of solid waste materials using a nanocomposite excitation solution according to claim 1, characterized in that: The solid waste material slurry after the mineralization reaction in step 7 is poured into the mold, and then cured to obtain a solid waste filling material sample. The curing temperature is 20 o C~25 o C, curing humidity is 90%~95%, and compressive strength is 2.5MPa~8.8MPa.
8. A solid waste filling material prepared by the method for strengthening the mineralization of solid waste materials using the nanocomposite excitation solution as claimed in claim 1.
9. An application of the solid waste filling material according to claim 8, characterized in that: The solid waste material slurry after the mineralization reaction is poured into a mold to make a goaf support structure; or the solid waste material slurry after the mineralization reaction is poured into the goaf for carbon fixation and backfilling.
Citation Information
Patent Citations
Alkali-activated cementing material and preparation method thereof
CN108249788A
Cited By
Micro-nano bubble reinforced system for mineralizing carbon dioxide by base solid waste and application method of micro-nano bubble reinforced system
CN120664853A
System for strengthening carbon dioxide mineralization of alkali-based solid waste by micro-nano bubbles
CN120664853B